2022
DOI: 10.3389/fpls.2022.813863
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Production Affects Blueberry Fruit Texture and Storability

Abstract: Ethylene, produced endogenously by plants and their organs, can induce a wide array of physiological responses even at very low concentrations. Nevertheless, the role of ethylene in regulating blueberry (Vacciniumspp.) ripening and storability is still unclear although an increase in ethylene production has been observed in several studies during blueberry ripening. To overcome this issue, we evaluated the endogenous ethylene production of aVacciniumgermplasm selection at different fruit ripening stages and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…Blueberry fruit exhibits a dark green colour during fruit growing stages, followed by de‐greening at the onset of ripening, and then achieves its desirable colour with successive anthocyanin accumulation (Zifkin et al ., 2012 ). Several studies have suggested that blueberry fruit possibly shows climacteric features, implying an important role of ethylene in blueberry fruit colouration (Colle et al ., 2019 ; Farneti et al ., 2022 ; Gupta et al ., 2015 ; Wang et al ., 2018b , 2022b ; Yan et al ., 2020 ). In the present study, we provided evidence to support the scenario that VcSPL12 negatively regulates ethylene production to affect blueberry fruit coloration by directly inactivating the expressions of VcACO6 and VcACS1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blueberry fruit exhibits a dark green colour during fruit growing stages, followed by de‐greening at the onset of ripening, and then achieves its desirable colour with successive anthocyanin accumulation (Zifkin et al ., 2012 ). Several studies have suggested that blueberry fruit possibly shows climacteric features, implying an important role of ethylene in blueberry fruit colouration (Colle et al ., 2019 ; Farneti et al ., 2022 ; Gupta et al ., 2015 ; Wang et al ., 2018b , 2022b ; Yan et al ., 2020 ). In the present study, we provided evidence to support the scenario that VcSPL12 negatively regulates ethylene production to affect blueberry fruit coloration by directly inactivating the expressions of VcACO6 and VcACS1 .…”
Section: Discussionmentioning
confidence: 99%
“…The colour change accompanied by anthocyanin accumulation is a critical process for the quality formation of blueberry fruit, making it an ideal material for studying fruit colouration (Zifkin et al ., 2012 ). While several transcriptional regulators and phytohormones have been documented to be implicated in regulating anthocyanin biosynthesis in blueberry fruit, knowledge regarding the regulatory network underlying the entire process of colour change is still limited (Farneti et al ., 2022 ; Jaakola et al ., 2010 ; Karppinen et al ., 2021 ; Lafferty et al ., 2022a , b ; Wang et al ., 2022b ; Xie et al ., 2022 ; Zifkin et al ., 2012 ). In a previous study, we demonstrated that VcMIR156a can influence anthocyanin and chlorophyll accumulation through its direct target VcSPL12 in tomato and Arabidopsis (Li et al ., 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…In litchi, ethylene plays a more important role in chlorophyll degradation in comparison with abscisic acid [44]. During blueberry ripening and storage, the role of ethylene in pigment and texture changes is genotype-dependent [45,46]. Nevertheless, the progress concerning the ethylene-induced molecular change in non-climacteric ripening is still slow, although extensive literature research has been reported on ethylene regulating non-climacteric ripening from physiological aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Further, ethylene signaling components are functional during blueberry fruit ripening [ 39 ]. An evaluation of 12 highbush blueberry cultivars indicated variation in ethylene production during fruit ripening across genotypes [ 40 ]. In this study, we further explored the role of ethylene in blueberry ripening by performing transcriptome analysis on fruit treated with ethephon (2-chloroethane phosphonic acid), an ethylene releasing plant growth regulator (PGR).…”
Section: Introductionmentioning
confidence: 99%